Discussion on the Evolution of Sea Reclamation from 2006 to 2018 in Jimo District, Qingdao, Shandong Province. Issue 1 (February 2021) - Xiu, Chun; Lu, Xin; Huo, Suxia; Li, Zhengxu; Ma, Tianran; Chen, Keke
Abstract: Sea reclamation is an important way to develop marine resources and expand land space. Based on the extraction technology of remote sensing image, the spatial distribution and evolution of sea reclamation in Jimo District from 2006 to 2018 were discussed. From 2006 to 2018, the reclamation area of Jimo District increased by 32.68km 2 . The industrial structure adjustment, the implementation of major projects and the increase of population were the main driving forces. The reclamation areas are mainly located in Aoshan Bay, Hengmen Bay and Xiaodao Bay, which occupy the former tidal flat and wetland resources of these bays and cause the change of the hydrodynamic environment. At the same time, the problems of land idle and low intensive utilization still remain. In the face of these problems, some measures, such as establishing and improving a long-term monitoring mechanism, reducing the stock of reclamation in accordance with the principles of economization and strengthening the ecological restoration of coastal zones, should be taken.